2022
DOI: 10.1155/2022/9405262
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Experiment to Evaluate the Impact of Multistage Load and Osmotic Pressure on Anchor Bolt

Abstract: In this paper, uniaxial compression tests, multistage loading tests, and electrochemical tests were adopted to investigate the strain characteristics, failure characteristics, and electrochemical impedance of anchor bolts in a cement-gypsum composite. The uniaxial compression test results showed that the uniaxial compressive strength σ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the cable tendon reinforcement system, the grout in the borehole is paramount [35]. Specifically, the stress at the bolt/grout (B/G) and grout/rock (G/R) faces is responsible for the force-transferring mechanism [36].…”
Section: Force-transferring Processmentioning
confidence: 99%
“…In the cable tendon reinforcement system, the grout in the borehole is paramount [35]. Specifically, the stress at the bolt/grout (B/G) and grout/rock (G/R) faces is responsible for the force-transferring mechanism [36].…”
Section: Force-transferring Processmentioning
confidence: 99%
“…e results showed that the corrosion rate was dependent on temperature. e electrochemical analysis method was used in the experimental measurement of anchor under osmotic pressure [28]. Sohail et al [29] conducted electrochemical test research on different types of reinforcement under corrosion conditions.…”
Section: Introductionmentioning
confidence: 99%